Optimizing Port Operations: A Literature Review of the Relationship between Facility Management, Human Resources, Licensing, Loading and Unloading Productivity, and Port Performance in Maritime Transportation: Mengoptimalkan Operasi Pelabuhan: Tinjauan Literatur tentang Hubungan antara Manajemen Fasilitas, Sumber Daya Manusia, Perizinan, Produktivitas Bongkar Muat, dan Kinerja Pelabuhan dalam Transportasi Maritim - Laju, I Kadek; Kurniadi, Dedy; Krisnawati, Luri; Sariyulis; Wijaya, Kukuh Wirahadi (PT. Alpha Trianguli Australis, 2024)
Port operations are crucial for maintaining efficient maritime transportation. Factors such as facility management, human resources, and licensing have a significant impact on port productivity and overall performance. Differences in management approaches, human resource involvement, and licensing regulations can lead to variations in productivity between ports. This study aims to conduct a comprehensive literature review to understand the relationship between these factors and identify best practices for optimizing port operations. The research method involves analyzing literature on port management, human resources, licensing, stevedoring productivity, and port performance. The results indicate that integrating careful facility management, competent human resource management, and strict licensing compliance can significantly improve port productivity and overall performance. These findings have important implications for developing strategies and policies to optimize port operations and improve the efficiency of maritime transportation.